Tropical Hospitality, British Masculinity, and Drink in Late Eighteenth-Century Jamaica - Burnard, Trevor (Historical Journal, 2022)
Abstract: White Jamaicans developed a drinking culture that drew on British precedents, but which mutated in the tropics into a form of sociability different from how sociability operated in mid-eighteenth Enlightenment Europe, where civility was a much-aspired-to norm. In this article, I use works by eighteenth-century social commentators on Jamaica – Edward Long and especially J. B. Moreton – to explore how white Jamaicans developed a form of sociability which in Long was praised as showing Jamaicans as a generous and hospitable people but which in Moreton was described, more accurately, as a distinctive and unattractive form of debauchery, oriented around excessive drinking and sexual exploitation of enslaved women and free women of colour. The overwhelming importance of slavery in Jamaica accentuated the trends towards a debauched version of hospitality that stressed white male pleasure over everything else as a central animating value in society.